The Effect Of Profitability, Financial Distress And Lotteryness On Stock Return On Properties And Real Estate Companies Listed On The Stock Exchange Indonesia Period 2019-2023 - Nuzul Nidaul Fitrah Usman; Rika Dwi Ayu Parmitasari; Rusnawati (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study intends to look at the effect of profitability, financial distress and lotteryness on stock returns in property and real estate companies listed on the Indonesia Stock Exchange in the 2019-2023 period. The research principle applied is a quantitative approach using multiple regression analysis. The sample collection technique uses Purposive Sampling. This study utilizes the SPSS application to process data that requires financial statements and stock prices from 10 companies studied. The results of the study revealed that profitability, financial distress and lotteyness simultaneously had a positive and significant impact on stock returns, which means that the hypothesis was accepted. Then, profitability has a negative and significant impact on stock returns, which means that the hypothesis is rejected. In addition, financial distress has a positive and significant impact on stock returns, which means that the allegations are rejected. And lastly, lotteryness has a positive and significant impact on stock returns which means that assumptions are approved. These findings indicate that increasing profitability and managing more stable financial conditions can increase investors' perception of the company's performance. In addition, understanding market perception of stocks that have lottery characteristics can be part of a communication and risk management strategy, especially in managing investor expectations for potential returns and risks.